FACTORS IN RELIGIOUS CULTURE TO INCREASE TOLERANT ATTITUDE OF GEN-Z AMONG URBAN MUSLIMS - Mutaqin, Mumu Zainal; Lestari, Dirga Ayu; Solihin, Solihin; Al-Ayyubi, Ibnu Imam; Rahmawati, Siti (AKADEMIKA: Jurnal Pemikiran Islam, 2024)
The purpose of this research is to dig deeper into the supporting and inhibiting factors of pluralism-oriented religious culture among Gen-Z both in the school environment, family, and society in order to have a tolerant attitude in their lives. This research, using qualitative with a descriptive approach that emphasizes efforts to obtain information about the situation, and symptoms that arise at the time of the research. Provides a description of an existing phenomenon, and can provide information related to the object under study. Data collection techniques through interviews, observation and documentation. The data analysis used is data reduction, data presentation and data verification. The results and discussion of the supporting and inhibiting factors of a pluralism-oriented religious culture among Gen-Z in Serang City can appreciate differences and respect ethnicity and religion so that they have a tolerant attitude towards others. Supporting and inhibiting factors are schools including the principal, and curriculum and PAI Teachers. Family includes religious education and parental involvement. While the community is in the form of a social environment that integrates religious values and seeks to support the development of spirituality. The inhibiting factors are teachers and education personnel and school facilities, school environment and student diversity.